2022
DOI: 10.3390/su14031933
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities, Quality Factors, and Required Changes during the Pandemic Based on Higher Education Leaders’ Perspective

Abstract: The pandemic period in education brought many challenges to all organizations. The activities of the higher educational institutions are being affected and the situation can last for a longer time. Under these circumstances, it is important to shift to online learning and improve educational processes through all organizational levels. The organizations had to assure appropriate distance or remote learning process by identifying their opportunities, meeting challenges, and identifying the sustainable quality f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…The activities of higher education institutions are being negatively impacted, and the situation may last for an extended period. Under these conditions, it is essential to transition to online classes and enhances educational processes at all levels of an organization [9]. With its rapid global spread and concomitant death toll, the COVID-19 pandemic represents an unprecedented global public health emergency not witnessed in the last century.…”
Section: Related Literature and Studiesmentioning
confidence: 99%
“…The activities of higher education institutions are being negatively impacted, and the situation may last for an extended period. Under these conditions, it is essential to transition to online classes and enhances educational processes at all levels of an organization [9]. With its rapid global spread and concomitant death toll, the COVID-19 pandemic represents an unprecedented global public health emergency not witnessed in the last century.…”
Section: Related Literature and Studiesmentioning
confidence: 99%
“…The COVID-19 pandemic has changed the rules of modern education. Many universities, for example [ 35 , 36 , 48 , 49 ], due to pandemic conditions, have started to use and spread a new, innovative e-learning approach to the education process. It has completely changed the conditions of modern education and may have long-lasting effects on the possibility and use of innovative solutions in modern high education [ 50 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on analysis of the literature [ 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], the authors have found the research gap in the case of the influence of the COVID-19 pandemic on the use of innovative e-learning tools in high education. The main problem that was analyzed in the paper was the influence of the COVID-19 pandemic on the change in the usage of innovative e-learning tools in university education.…”
Section: Introductionmentioning
confidence: 99%
“…Facing and understanding several problems and obstacles led to the completion of work connected to an important and appealing issue, trade and machine learning. The information gathered to get a better understanding of the subject is supplemented with more in-depth resources to get to the point and cross the gap between finance and information technology (Dagiene et al 2022 ). The existing studies made use of the economic approaches to predict the financial market rate and these models have one major drawback: they model the complex and nonstationary nature of the stock market via linear and stationary assumptions (Sokolov-Mladenović et al 2017 ; Li et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%